In vivo Evidence for Brain Region-Specific Molecular Interactions Between Cannabinoid and Orexin Receptors - Kim, Hye Ji J.; Zagzoog, Ayat; Smolyakova, Anna Maria; Ezeaka, Udoka C.; Benko, Michael J.; Holt, Teagan; Laprairie, Robert B. (Frontiers in Neuroscience, 2021)
The endocannabinoid and orexin neuromodulatory systems serve key roles in many of the same biological functions such as sleep, appetite, pain processing, and emotional behaviours related to reward. The type 1 cannabinoid receptor (CB1R) and both subtypes of the orexin receptor, orexin receptor type 1 (OX1R) and orexin receptor type 2 (OX2R) are not only expressed in the same brain regions modulating these functions, but physically interact as heterodimers in recombinant and neuronal cell cultures. In the current study, male and female C57BL/6 mice were co-treated with the cannabinoid receptor agonist CP55,940 and either the OX2R antagonist TCS-OX2-29 or the dual orexin receptor antagonist (DORA) TCS-1102. Mice were then evaluated for catalepsy, body temperature, thermal anti-nociception, and locomotion, after which their brains were collected for receptor colocalization analysis. Combined treatment with the DORA TCS-1102 and CP55,940 potentiated catalepsy more than CP55,940 alone, but this effect was not observed for changes in body temperature, nociception, locomotion, or via selective OX2R antagonism. Co-treatment with CP55,940 and TCS-1102 also led to increased CB1R-OX1R colocalization in the ventral striatum. This was not seen following co-treatment with TCS-OX2-29, nor in CB1R-OX2R colocalization. The magnitude of effects following co-treatment with CP55,940 and either the DORA or OX2R-selective antagonist was greater in males than females. These data show that CB1R-OX1R colocalization in the ventral striatum underlies cataleptic additivity between CP55,940 and the DORA TCS-1102. Moreover, cannabinoid-orexin receptor interactions are sex-specific with regards to brain region and functionality. Physical or molecular interactions between these two systems may provide valuable insight into drug-drug interactions between cannabinoid and orexin drugs for the treatment of insomnia, pain, and other disorders.